Enabling Environment Endline Assessment : Indonesia - Robinson, Andy (World Bank, Washington, DC, 2014)
The Water and Sanitation Program (WSP) has implemented the Global Scaling up Rural Sanitation Project since 2007. One of the central objectives of the project is to improve sanitation at a scale sufficient to meet the 2015 sanitation Millennium Developmental Goal (MDG) targets in Indonesia, India, and Tanzania. The baseline assessment of the enabling environment was completed in July and August 2007, during the start-up phase of the overall project. This follow up endline assessment was carried out three years later in mid-2010. This report presents the main findings and recommendations from the endline assessment of the ability of the enabling environment to scale up, sustain, and replicate sanitation improvements in East Java, Indonesia. Community-Led Total Sanitation (CLTS) was introduced into Indonesia in May 2005 through field trials in six provinces.The remarkable success of these field trials, implemented with assistance from the Ministry of Health (MoH) and two of its large rural water supply and sanitation programs, caused the CLTS approach to spread to several hundred additional communities, generated significant demand from other districts, and led to its subsequent adoption as the main methodology for sanitation improvement in several large sector programs. Sanitation remains a local government responsibility, and as a result the decentralized and demand-responsive approach adopted by the project in East Java has proved highly appropriate and effective. In the absence of any larger central programs, district governments were convinced to use their own institutions and resources to implement the project, resulting in sustainable arrangements and finance, cost-effective use of local resources, as well as proactive efforts to learn from others, innovate, and develop locally appropriate approaches. The private resource agencies contracted by the project were effective in supporting the districts during this learning and development phase, and most district governments now appear to be confident in managing and sustaining their rural sanitation programs. There is increasing consensus nationally that total sanitation and sanitation marketing approaches are effective program methodologies, with most rural sanitation programs in Indonesia now utilizing some form of total sanitation approach and many showing interest in developing a sanitation marketing component.